PENGARUH WORKLIFE BALANCE DAN BUDAYA PERUSAHAAN TERHADAP KINERJA KARYAWAN (Studi pada Divisi Sumber Daya Manusia PT BIO FARMA (Persero) - Anggara, Rivaldi Wira; Winarno, Alex (IMAGE : Jurnal Riset Manajemen, 2020)
The problem of employee performance in the Human Resources (HR) Division of PT Bio Farma (Persero) which has not yet reached the target is the main issue in this study. Worklife balance (WLB) variables and the implementaion of company culture (CC) are considered as factors that influence it. The research objective is to measure the effect of WLB and CC on the performance of employees. This research uses quantitative methods, using descriptive analysis and regression. Data obtained by sampling technique saturated with a sample of 30 employees in the HR division. Descriptive analysis results are known that the level of performance and CC are in the good and strong category, while the WLB variable is in the very good category. The results of the regression analysis showed that WLB and CC partially had a positive effect of 18.87% and 51.63%. Simultaneously the two variables studied have a significant effect on employee performance by 70.5%.Â Keywords: Worklife Balance; Corporate Culture; Employee Performance.